Pengaruh Study From Home dan Fasilitas Belajar di Rumah terhadap Motivasi Belajar Siswa Kelas X OTKP SMKN 1 Sooko Mojokerto - Cindy Erlinda Mayangsari; Durinda Puspasari (Edunusa: Journal of Economics and Business Education, 2022)
The purpose of this research is to analyze: 1) the influence of studying from home on students’ learning motivation for Indonesian correspondence subject at class X OTKP SMKN 1 Sooko Mojokerto; 2) the influence of learning facilities at home on students' learning motivation for Indonesian correspondence subject at class X OTKP SMKN 1 Sooko Mojokerto; 3) the influence of studying from home and learning facilities at home on students’ learning motivation for Indonesian correspondence subject at class X OTKP SMKN 1 Sooko Mojokerto. This research was quantitative research. Data collection techniques which used were questionnaire and interview. The population in this reasearch were all of 102 students at class X OTKP SMKN 1 Sooko Mojokerto. The sample in this research was 81 students used proportional random sampling. The instrument trial in this research consists of a validity test and a reliability test. The data analysis techniques which used in this reaserch were: 1) classical assumption test which consists of normality test, multicollinearity test, and heteroscedasticity test; 2) hypothesis test used multiple linear regression. The results of  research showed that: 1) there was a significant effect of studying from home on the students' learning motivation for Indonesian correspondence subject at class X OTKP SMKN 1 Sooko Mojokerto; 2) there was a significant effect of learning facilities at home on students' learning motivation for Indonesian correspondence subject at class X OTKP SMKN 1 Sooko Mojokerto; 3) there was a significant effect of studying from home and learning facilities at home on students' learning motivation for Indonesian correspondence subject at class X OTKP SMKN 1 Sooko Mojokerto.